The Relationship Between Measurements Of Medial Tibial Plateau Depth And Femoral Notch (Notch Witdh & Shape) On Genu Mri And The Severity Of The Isolated Anterior Cruciate Ligament Tear Cross Sectional Study At Tertiary Refferal Hospital Dr. Moewardi General Hospital & Prof. Soeharso Orthopedic Hospita - Irawan, Amelia Tjandra; Adhie, Anistyaning Wahyu; Anindyarani, Yutrisa Sasti; Lillah, Yudhi (Indonesian Basic and Experimental Health Sciences, 2024)
Background: The knee is a complex joint, composed of ligament components, one of which is the Anterior cruciate ligament which functions as a knee stabilizer. ACL injury is the most common ligament injury in the knee joint. Anatomical factors are one of the factors that predict the severity of an ACL tear. Medial Tibial Plateau Depth and Femoral Notch are one of the influencing factors. Genu MRI examination plays an important role in assessing these factors regarding the severity of an Isolated ACL tear. Objective: To determine the relationship between measurements of Medial Tibial Plateau Depth and Femoral Notch (Notch Witdh & Shape) on MRI genu with the severity of Isolated Anterior Cruciate Ligament Tear at Dr. Moewardi Hospital Surakarta and Prof. Soeharso Orthopedic Hospital Surakarta Method: Quantitative analytical research with a cross-sectional design was conducted from May to June 2023. The research sample was patients who underwent a Knee MRI examination with clinical Isolated ACL Tear in the period 1 January 2021 to 30 June 2023. Patients were assessed for the severity of the ACL tear and measurements of the Medial Tibial Plateau Depth and Notch Width and the shape of the Femoral Notch Os Femur Results: Medial tibial plateau depth on MRI Genu was positively correlated with the severity of isolated ACL tear (p value <0.001 and r correlation value of 0.943). Femoral Notch Shape, especially the A shape, has a relationship with the severity of isolated ACL tear (p value = 0.036 (p < 0.05) and r value = 0.274). Meanwhile, the relationship between femoral notch width on MRI Genu and the degree of isolated ACL tear is not significant because the p value obtained is 0.484 (p>0.05) Conclusion: Medial Tibial Plateau Depth and Femoral Notch Shape on MRI Genu have a relationship with the Severity of Isolated Anterior Cruciate Ligament Tear, whereas Femoral Notch Witdh has no relationship